2020
DOI: 10.1093/rb/rbaa026
|View full text |Cite
|
Sign up to set email alerts
|

Utility of direct 3D co-culture model for chondrogenic differentiation of mesenchymal stem cells on hyaluronan scaffold (Hyaff-11)

Abstract: This study presents direct 2D and 3D co-culture model of mesenchymal stem cells (MSCs) line with chondrocytes isolated from patients with osteoarthritis (unaffected area). MSCs differentiation into chondrocytes after 14, 17 days was checked by estimation of collagen I, II, X, aggrecan expression using immunohistochemistry. Visualization, localization of cells on Hyaff-11 was performed using enzymatic technique and THUNDER Imaging Systems. Results showed, that MSCs/chondrocytes 3D co-culture induced suitable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…HyaloFast ® is based on a semisynthetic insoluble polymer obtained by the esterification of all carboxyl groups of HA with benzyl alcohol (HYAFF-11 ® ). It was previously shown that HYAFF-11 ® provides an appropriate environment, supporting growth, migration, proliferation, and differentiation of MSCs into chondrogenic lineage [30][31][32]. Successful fabrication of tissue-engineered osteochondral grafts has been shown for MSCs loaded into a HYAFF-11 ® sponge [33].…”
Section: Discussionmentioning
confidence: 99%
“…HyaloFast ® is based on a semisynthetic insoluble polymer obtained by the esterification of all carboxyl groups of HA with benzyl alcohol (HYAFF-11 ® ). It was previously shown that HYAFF-11 ® provides an appropriate environment, supporting growth, migration, proliferation, and differentiation of MSCs into chondrogenic lineage [30][31][32]. Successful fabrication of tissue-engineered osteochondral grafts has been shown for MSCs loaded into a HYAFF-11 ® sponge [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, with regard to a clinical application, the measurement, automatic documentation and any necessary automatic adaption of the resulted electric fields would have to be enabled in the future. In addition, in the literature it is described that a co-cultivation of chondrocytes and mesenchymal stem cells could also lead to improved cartilage regeneration [ 60 , 61 ]. Since mesenchymal stem cells also react to electric fields with chondrogenesis [ 62 , 63 ], a combination of electrical stimulation with mechanical loading, a suitable 3D scaffold close to cartilage properties as well as the use of co-cultivated cells could lead to an optimal basis for re-implantation of cultivated autologous chondrocytes into the cartilage defect.…”
Section: Discussionmentioning
confidence: 99%
“…As iPSCs can overcome the limitations of previous types of PSCs with additional benefits, they are expected to play a more diverse role in regenerative medicine. For joint-related disease modeling and 3D model construction, patient-specific iPSCs surpass the limitations presented by animal models (interspecies differences, i.e., etiology) and chondrocyte culture (more complicated harvesting procedures, less realistic model, For joint-related disease modeling and 3D model construction, patient-specific iPSCs surpass the limitations presented by animal models (interspecies differences, i.e., etiology) and chondrocyte culture (more complicated harvesting procedures, less realistic model, rapid dedifferentiation in vitro) [15,16]. Regarding the clinical applications of stem cells, iPSCs can be generated from several different somatic cells to avoid any complicated harvest procedures and minimize ethical conflicts in contrast to ESCs and adult stem cells.…”
Section: Induced Pluripotent Stem Cells (Ipscs) and Their Advantagesmentioning
confidence: 99%